Lâminas em alto relevo para o ensino de ondas e fenômenos Ondulatórios a deficientes visuais - Silva, Alexandre Chaves da (Universidade Federal Rural do Semi-Árido, 2018)
This dissertation presents the planning, elaboration and testing of an educational product entitled High-Relief Sheets for Teaching Waves and Ondulatory Phenomena to Visual Deficients. Forty-seven high-relief sheets were made of plastic material with the use of commercial punches like center punch of 5 mm (used for the contour of the images), PZ1 (used for curves representation) and T10 (used to emphasize points or structures different from the previous ones). The basic content of what is usually called ondulatory in the textbooks of high school was covered. The product was tested in ten one-hour and forty-minute classes given to a totally visual impaired student, whose prior knowledge of the subject was evaluated through a pre-test with questions from the National High School Examination (ENEM, in Portuguese). At the end of the test, the student's conceptual appropriation was evaluated through a post-test, with five questions extracted from the pre-test and five other questions also extracted from the ENEM, but different from those used in the pre-test. From the student's post-test performance, and from his evident satisfaction, expressed in several comments, it is believed that the product is potentially useful for large-scale use
Keywords: Ensino de Física; Ondas; Fenômenos Ondulatórios; Deficiente Visual; Método Braille; Physics Teaching; Waves; Ondulatory Phenomena; Visual Deficients; Braille Method; CIENCIAS EXATAS E DA TERRA::FISICA